ATP-Dependent Chromatin Remodeling by the Cockayne Syndrome B DNA Repair-Transcription-Coupling Factor - Citterio, Elisabetta (American Society for Microbiology, 2000)
The Cockayne syndrome B protein (CSB) is required for coupling DNA excision repair to transcription in a process known as transcription-coupled repair (TCR). Cockayne syndrome patients show UV sensitivity and severe neurodevelopmental abnormalities. CSB is a DNA-dependent ATPase of the SWI2/SNF2 family. SWI2/SNF2-like proteins are implicated in chromatin remodeling during transcription. Since chromatin structure also affects DNA repair efficiency, chromatin remodeling activities within repair are expected. Here we used purified recombinant CSB protein to investigate whether it can remodel chromatin in vitro. We show that binding of CSB to DNA results in an alteration of the DNA double-helix conformation. In addition, we find that CSB is able to remodel chromatin structure at the expense of ATP hydrolysis. Specifically, CSB can alter DNase I accessibility to reconstituted mononucleosome cores and disarrange an array of nucleosomes regularly spaced on plasmid DNA. In addition, we show that CSB interacts not only with double-stranded DNA but also directly with core histones. Finally, intact histone tails play an important role in CSB remodeling. CSB is the first repair protein found to play a direct role in modulating nucleosome structure. The relevance of this finding to the interplay between transcription and repair is discussed.